Researching situated learning: Participation, identity and practices in client-consultant relationships - HANDLEY, Karen (Institutional Knowledge at Singapore Management University, 2007)
Situated learning theory has emerged as a radical alternative to conventional cognitivist theories of knowledge and learning, emphasizing the relational and structural aspects of learning as well as the dynamics of identity construction. However, although many researchers have embraced the theoretical strengths of this perspective, methodological and operational issues remain undeveloped in the literature. This article seeks to address these deficiencies by developing a conceptual framework informed by situated learning theory and by investigating the methodological implications. The framework is applied in the context of an empirical study of how management consultants learn the practices and identities appropriate to clientconsultant projects. By presenting two vignettes and interpreting them using the conceptual framework, we show how learning is regulated by the consulting firm as well as individuals themselves, and that, paradoxically, 'failure to learn' may be an outcome of consultants' efforts to construct a coherent sense of self.